2021
DOI: 10.29374/2527-2179.bjvm002120
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the right ventricular function in dogs with brachycephalic syndrome before and after rhinoplasty

Abstract: Brachycephalic dogs are usually affected by primary and secondary anatomical changes in the airways that contribute to the brachycephalic syndrome. Chronically, these changes contribute to an increase in pulmonary arterial pressure and right cardiac overload (cor pulmonale). The right cardiac function in 17 dogs with brachycephalic syndrome was assessed using echocardiography before, and at 30 and 60 days after rhinoplasty. The maximum pulmonary systolic flow velocity, the pressure gradient between the AP and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
1
2
0
Order By: Relevance
“…However, no significant differences between BOAS- and BOAS+ or BOAS Grades in pugs could be found in the present study. This is in accordance with findings of the study by Hainfellner et al (2021), in which there was no significant change in TAPSE before compared to after rhinoplasty [ 48 ]. When further comparing measurements of TAPSE in pugs to those of interbreed references, overall, lower TAPSE and TAPSE:Ao values were detected in pugs than in previous studies of various breeds, even when compared to an RI of a similar BW [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…However, no significant differences between BOAS- and BOAS+ or BOAS Grades in pugs could be found in the present study. This is in accordance with findings of the study by Hainfellner et al (2021), in which there was no significant change in TAPSE before compared to after rhinoplasty [ 48 ]. When further comparing measurements of TAPSE in pugs to those of interbreed references, overall, lower TAPSE and TAPSE:Ao values were detected in pugs than in previous studies of various breeds, even when compared to an RI of a similar BW [ 41 , 42 ].…”
Section: Discussionsupporting
confidence: 93%
“…This aforementioned study found no evidence of changes in PAP in dogs with Brachycephalic Syndrome and no explanation for lower pulmonic velocities. In another study, 16 brachycephalic dogs (four pugs and 12 French Bulldogs) underwent rhinoplasty, and RV function as well as pulmonic velocity and pressure gradient between pulmonary artery and right ventricle was examined via echocardiography before and after surgery [ 48 ]. This study revealed a significant increase in Pvel and a change in pressure gradient after rhinoplasty, and they hypothesised this may be due to a reduction of the upper airway obstruction and consequently a decrease of pulmonary vascular resistance.…”
Section: Discussionmentioning
confidence: 99%
“…However, no studies have been published on whether rhinoplasty and folded-flap palatoplasty affect cardiac morphology and function. Evaluation of right ventricular function 30 and 60 days after rhinoplasty showed that the elevated values of fractional area change of the right ventricle normalized 60 days after the procedure ( 24 ). Therefore, we aimed to compare echocardiographic variables in brachycephalic dogs before and six to 12 months after surgical correction of BOAS and also to compare them with echocardiographic variables in non-brachycephalic control dogs.…”
Section: Introductionmentioning
confidence: 99%